SOSIALISASI TENTANG WEWENANG KEPALA DESA SEBAGAI HAKIM PERDAMAIAN DESA DALAM PENYELESAIAN SENGKETA TANAH DI DESA KUIMASI KECAMATAN FATULEU KABUPATEN KUPANG - A. Resopijani; Reny R. Masu; Daud Y. Dollu; Alexander S. Pally (Jurnal Abdi Insani, 2023)
Community Service is a duty and responsibility that must be carried out by a tertiary institution, the community as the owner of higher education gets contributions from the results of scientific deepening and development that have been carried out in the Tri Dharma, namely education and teaching and research and Community Service. Based on the Tri Dharma, it is the obligation of each unit in Higher Education to implement the knowledge that has been obtained and applied in the teaching and learning process, but it is necessary to apply it in people's lives. The objectives to be achieved from this research are: 1. Increase the knowledge and understanding of the village head and the community regarding the role of the village head as a judge for village peace according to the applicable laws and regulations concerning the village. 2. Understanding the roles and mechanisms in handling land disputes 3. Conforming perceptions about the approach needed in handling land disputes that can be applied by the village head as the Village Peace Judge. The process of implementing the activity begins with an opening by the Head of the section and the Village Head and a prayer by the officer, then it is continued with the presentation of material which begins with introductions, followed by discussion with the delivery of material by resource persons and questions and problems raised by participants or members of the community. The material was delivered by resource persons from specializing in Procedural Law as a Panel, using the lecture, discussion and dispute handling method using the case study method by providing opportunities for people who have ongoing or new land disputes or have already been resolved, the approach used is to apply a justice approach restorative justice or mediation/deliberation to reach a consensus until a peace agreement is reached. This activity was carried out in the village of Kuimasi, Fatuleu District, Kupang Regency, on Monday, May 26 2023, with the theme: Legal Counseling and Implementation of handling land disputes. Participants consisted of Village Officials and the Kuimasi Village community as well as traditional leaders and Kuimasi village community leaders. In practice, the community gave a very positive response to this activity, as evidenced by the large number of participants who attended and responded by asking questions related to the problems experienced. This activity had a very positive impact because local residents did not understand the mechanisms for handling land disputes in the village, and the servants were present to provide an overview of the mechanisms and regulations for handling land disputes in the village and were able to answer some of the problems that were often experienced in the village.